Characterizations for Certain Subclasses of Starlike and Convex Functions Associated with Lommel, Struve and Bessel Functions - Shelake, G. D.; Joshi, S. B.; Sangle, N. D. (Nepal Journal of Mathematical Sciences, 2022)
In this paper we have determined some necessary and sufficient conditions of normalized Lommel function sμ,v, Struve function hv and Bessel function jv of the first kind to be in the subclasses S(α, β, γ) and K(α, β, γ) of starlike and convex functions of order α and type β, γ, in the unit disk U.